(untitled) (Journal Of Educational and Psychological Researches, 2014)
In spite of the disappearing of a clear uniform textbook for teaching ESP at different departments and different colleges in both scientific and humanistic studies, the practitioners at those departments and colleges have to teach translation as one of the important requirements to pass the English language exam. The lack of defined translation activities is a noticeable problem therefore; the problem of teaching translation is diagnosed in that the students lack the ability to comprehend the text in English language and other translation knowledge and skills. The study aims to suggest a translation strategy and then find out the effect of the translation strategy on ESP learners’ achievement in translation. A sample of 50 students from university of Baghdad / College of Education for Women / Department of Educational and Psychological Sciences has been selected and distributed into control and experimental groups. The results show that there are statistically significant differences between the control and experimental groups’ achievement in translation post test in favor of experimental group.